Normal Coordinate Analysis and Evaluation of Molecular Constants of Chlorodifluoro Methane and its Isotopes - Natarajan, A.; Ebenezer, J.S.P.; Delano Bernabas Ilango, C. (Asian Journal of Chemistry, 2010)
The potential energy constants of chlorodifluoro-methane and its isotopes have been evaluated on the basis of GVFF using the very recently assigned vibrational frequencies. The other molecular constants such as mean square amplitudes of vibration, generalized mean square amplitudes of vibration, shrinkage constants, Coriolis coupling coefficients and the centrifugal distortion constants have also been computed for the first time. The findings are presented and discussed in brief.